EVERYDAY LIFE IN DAGESTAN AULS (1860-1917): HISTORICAL ASPECT - Dalgat, El'mira Murtuzalievna (History, Archeology and Ethnography of the Caucasus, 2024)
This study examines the history of everyday life in Dagestan auls during the late imperial period (second half of the 19th – early 20th centuries). Following the Caucasian War and Dagestan’s annexation to the Russian Empire, a series of administrative, peasant, and judicial reforms were implemented, impacting various spheres including economy, social relations, culture, and daily life. The research focuses on work, leisure, and private life in the auls. Methodologically, the study employs descriptive and comparative historical approaches, alongside the historical-genetic method to compare everyday life in Dagestan auls during the period under investigation with previous eras. Additionally, a modernization approach is utilized, viewing history as a transition process from traditional to modern society. The findings reveal that while certain modernization processes affected socio-economic relations and cultural life in Dagestan, traditional everyday life remained largely conservative. Centuries of adaptation to harsh natural and climatic conditions had shaped the traditional lifestyle, necessitating intense labor from both men and women. The historically established division of labor between genders, influenced by the need for men to defend auls against invaders, persisted even after Dagestan’s incorporation into the Russian Empire and the subsequent reduction in external threats. Regarding leisure and holidays, no significant changes were observed in the traditional Dagestani society. Similarly, private life remained largely unaltered, with clearly defined and strictly observed gender roles within families.
Keywords: Dagestan; aul; history of everyday life; labour; leisure; private life